Investment Knowledge and Income on Investment Decisions of the Boyolali Community - Laras Wulandari; Wikan Budi Utami; Iin Emy Prastiwi; Budiarso; Merliana Dewi Astuti (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
Investment is an important thing in today's era. Many things influence investment decisions including knowledge about investment itself and a person's income. This study aims to determine the effect of Investment Knowledge and Income on Investment Decisions of the Boyolali Community. This study is a quantitative study. using multiple linear regression analysis, through the swimmer test, validity test, reliability test, classical assumption test and F test. The population in this study were residents of Boyolali, Central Java. The sample of this study was 60 samples. The results of this study indicate that investment knowledge and income both have a partial effect on investment decisions.